2003
DOI: 10.1046/j.1365-2257.2003.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Single value of serum transferrin receptor is not diagnostic for the absence of iron stores in anaemic patients with rheumatoid arthritis

Abstract: Serum transferrin receptor (sTfR) concentrations were measured in anaemic patients with rheumatoid arthritis (RA). Serum transferrin receptor concentrations were positively correlated with the percentage of hypochromic cells and negatively correlated with MCH. There was a weak correlation with serum ferritin (sFn) concentration but not with reticulocyte count. Thus, high concentrations of sTfR indicate iron-deficient erythropoiesis rather than levels of storage iron in the tissues. Patients were divided into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 31 publications
1
1
0
5
Order By: Relevance
“…This study showed that CHr and sTfR are sensitive markers for the detection of iron deficiency erythropoiesis, in line with other authors (Mast et al. , 2002; Thomas & Thomas, 2002; Siebert et al. , 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This study showed that CHr and sTfR are sensitive markers for the detection of iron deficiency erythropoiesis, in line with other authors (Mast et al. , 2002; Thomas & Thomas, 2002; Siebert et al. , 2003).…”
Section: Discussionsupporting
confidence: 92%
“…В ранее выполненных исследованиях показана ключевая роль гепцидина, ключевого циркулирующего в крови пептида, как связующего звена между воспалением и обменом железа [20]. Напротив, в отношении sTfR имеются данные о том, что воспаление не влияет на его концентрацию, а увеличение его содержания в крови может свидетельствовать о сопутствующем дефиците железа у ревматологических больных [24].…”
Section: т а б л и ц аunclassified
“…В ранее выполненных иссле дованиях показана ключевая роль гепцидина, циркули рующего в крови пептида, как ключевого связующего звена между воспалением и обменом железа [10,17,18]. Напротив, в отношении sTfR имеются данные о том, что воспаление не влияет на его концентрацию, а уве личение его содержания в крови может свидетельст вовать о сопутствующем дефиците железа у больных [19]. В обеих группах больных с анемией показано увеличение концентрации гепцидина.…”
Section: материалы и методыunclassified